2003
DOI: 10.1002/prep.200390010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Energetic Materials 84: Pyrolysis of 5‐Substituted 1,3,5‐Trinitrohexahydropyrimidines

Abstract: Results of slow and fast pyrolysis were compared for 1,3,5‐trinitrohexahydropyrimidine compounds in which the 5‐position was substituted by H, CH3, NO2, CH2ONO2, and CH2N3. IR and Raman spectroscopy were used to identify and quantify all of the gaseous products. The decomposition process appears to be initiated by reactions at the 5‐position of the ring. The gases produced are rather similar for all of the compounds, however the different functional groups impart their own signature on the concentrations of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Related cyclic nitramines RDX and HMX melt, or undergo liquefaction, with decomposition rapidly enough that their heat of fusion cannot be obtained. Additionally, DNNC and RDX structural variation affects thermochemical properties related to rapid pyrolysis and simulated combustion behavior [4,38].…”
Section: Resultsmentioning
confidence: 99%
“…Related cyclic nitramines RDX and HMX melt, or undergo liquefaction, with decomposition rapidly enough that their heat of fusion cannot be obtained. Additionally, DNNC and RDX structural variation affects thermochemical properties related to rapid pyrolysis and simulated combustion behavior [4,38].…”
Section: Resultsmentioning
confidence: 99%
“…1) derivatives employed T-Jump/FTIR and Raman spectroscopy analyses at 0.5 MPa and 350 • C. Results suggested that the substituted groups at the 5-position largely control the pathway followed by the predominantly bimolecular decomposition process and determine the gaseous products observed [10]. Once again, no rate-controlling step was identified.…”
Section: Introductionmentioning
confidence: 99%
“…Hendrickson and Shackelford also performed thermo chemical decomposition studies on DNNC [11]. Pyrolysis of 5-substituted 1,3,5-trinitrohexahydropyrimidines was studied also by Roos and Brill [12]. The thermal stability of 1,3,5,5-tetranitrohexahydropyrimidine (DNNC, TNDA) in liquid phase under isothermal conditions was studied [4].…”
Section: Introductionmentioning
confidence: 99%